Design of a broadband Quasi-Yagi dipole - Yeo, Chun Beng (2015)
This report suggest the design, fabrication and testing of a Planar Quasi-Yagi dipole antenna using bow-tie element feed from a Microstrip Parallel Stripline Transition. The antenna is design to operate in the frequency band from 800MHz to 2100MHz with ƒc define at 1450MHz. The bandwidth of the antenna was specified to be about 90%. By incorporate the design of a Planar Quasi-Yagi dipole together with the Bow-tie element, the antenna have the advantages of the directional beam of a Yagi and the wide-band of a Bow-tie.